2016
DOI: 10.1152/ajpgi.00354.2015
|View full text |Cite
|
Sign up to set email alerts
|

Keratin 8 knockdown leads to loss of the chloride transporter DRA in the colon

Abstract: Asghar MN, Priyamvada S, Nyström JH, Anbazhagan AN, Dudeja PK, Toivola DM. Keratin 8 knockdown leads to loss of the chloride transporter DRA in the colon. Am J Physiol Gastrointest Liver Physiol 310: G1147-G1154, 2016. First published April 28, 2016 doi:10.1152 doi:10. /ajpgi.00354.2015 are intermediate filament proteins important in protection from stress. The roles of keratins in the intestine are not clear, but K8 knockout (K8 Ϫ/Ϫ ) mice develop a Th2-type colonic inflammation, epithelial hyperproliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 48 publications
2
16
1
Order By: Relevance
“…We had validated DRA antibodies utilizing DRA knockout 4 , keratin-8 knockout 16 and C. rodentium -infected mice 17 , where DRA expression is markedly reduced or is absent, as well as in Caco2 cells where DRA expression was knocked down by shRNA.…”
Section: Methodsmentioning
confidence: 99%
“…We had validated DRA antibodies utilizing DRA knockout 4 , keratin-8 knockout 16 and C. rodentium -infected mice 17 , where DRA expression is markedly reduced or is absent, as well as in Caco2 cells where DRA expression was knocked down by shRNA.…”
Section: Methodsmentioning
confidence: 99%
“…Studies of certain mutations, as well as knockdown and knockout experiments, have revealed that IFs containing heteropolymerization of type I (K18–K20 and K23) and type II (K7 and K8) keratins have roles in epithelial apical processes, such as transport and barrier functions . Such IFs are often also associated with desmosomes, which are instrumental in integration of apical components for cellular functions .…”
Section: Apical Intermediate Filaments That Are Closely Related To Otmentioning
confidence: 99%
“…99 Studies of certain mutations, as well as knockdown and knockout experiments, have revealed that IFs containing heteropolymerization of type I (K18-K20 and K23) and type II (K7 and K8) keratins have roles in epithelial apical processes, such as transport and barrier functions. 106,107 Such IFs are often also associated with desmosomes, which are instrumental in integration of apical components for cellular functions. 108 Since the TJ protein claudin-1 has been reported to be associated with keratin76, 106 the direct or indirect association of IFs with the TJapical complex is an obligatory subject for future study.…”
Section: Apical Intermediate Filaments That Are Closely Related To Otmentioning
confidence: 99%
“…A likely reason is that keratins fulfil a general scaffolding function for membrane proteins [ 122 ]. Very recently Asghar and co-workers [ 123 ] observed a complete loss of the apical localizing chloride transporter (DRA) explaining the strong diarrhea phenotype occurring in patients with inflammatory bowel disease. Furthermore, a direct connection between higher levels of microbiota-produced short chain fatty acids in stool and decreased levels of the monocarboxylate transporter 1 (MCT1) was shown in K8 −/− colon [ 124 ].…”
Section: Intermediate Filaments Mediating Barrier Function In Simpmentioning
confidence: 99%